PENGEMBANGAN TARI BUNGKUH DI SMP NEGERI 4 BATAHAN SATU ATAPDESA BATU SONDAT KECAMATAN BATAHAN KABUPATEN MANDAILING NATALPROVINSI SUMATERA UTARA - Yefni Sania Ulfa; Rosalina, Venny (Universitas Negeri Padang, 2026)
This study aims to describe the development of the Bungkuh Dance at SMP Negeri 4 Batahan Satu Atap, Batu Sondat Village, Batahan District, Mandailing Natal Regency, North Sumatra Province. The study used a qualitative approach with descriptive analysis methods. Data was obtained through literature studies, observations, interviews, and documentation, then analyzed through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the Bungkuh Dance experienced development in terms of quality and quantity. Quality development includes adding a variety of movements, variations in floor patterns, and updating costumes and makeup to better suit the needs of the performance. Meanwhile, quantity development is seen in the increase in the number of dancers and the expansion of the dance's function from wedding ceremony performances to educational performance dances in school environments. This development contributes to the preservation and sustainability of the Bungkuh Dance as a regional cultural heritage.